Repair of heat-damaged SCC cantilever beams using SNSM CFRP strips. (April 2020) - Ashteyat, Ahmed M.; Haddad, Rami; Obaidat, Yasmeen T.
Abstract: The potential of using side near surface mounted (SNSM) fiber reinforced polymer (FRP) for strengthening/repairing cantilever self-compacting concrete (SCC) beams was investigated. A total of twelve L-shaped reinforced SCC prototypes with a cantilever component (150x150x750 mm) were cast then cured for 28 days. Eight specimens were heated in an electric furnace at 400 °C and 500 °C for two hours with remaining four SCC specimens left at laboratory air, as controls. Control and heat-damaged cantilever beams were strengthened/repaired using single SNSM-CFRP strips, inserted in two parallel longitudinal man-made side grooves, located at 25 or 60 mm from the beams' top tension fiber. Another set of beams were strengthened/repaired using double strips, inserted in same grooves at 60 mm from the beams' top fiber or in duplicate grooves separated by 10 mm. The mechanical behavior of the SCC cantilever beams was evaluated under one-point static loading acting on the fee-end of the beams. Measurements of deflection at the beams' free-end and strain in SNSM CFRP strips were recorded as load was increased. SNSM CFRP strips' number and location, as well as the exposure temperature significantly impact mechanical performance of the present SCC cantilever beam. Inserting two SNSM CFRP strips in side grooves with spacing imparted the best contribution to mechanical response. The use of SNSM CFRP single strips at 25 mm helps averting concrete cover peeling-off prior to flexural failure as observed in the remaining repaired/strengthened SCC cantilever beams.